2021
DOI: 10.1038/s41467-021-26329-1
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic and structural roles for the surface in guiding SAS-6 self-assembly to direct centriole architecture

Abstract: Discovering mechanisms governing organelle assembly is a fundamental pursuit in biology. The centriole is an evolutionarily conserved organelle with a signature 9-fold symmetrical chiral arrangement of microtubules imparted onto the cilium it templates. The first structure in nascent centrioles is a cartwheel, which comprises stacked 9-fold symmetrical SAS-6 ring polymers emerging orthogonal to a surface surrounding each resident centriole. The mechanisms through which SAS-6 polymerization ensures centriole or… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
28
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(29 citation statements)
references
References 67 publications
1
28
0
Order By: Relevance
“…Compatible with this notion, rational mutagenesis of Chlamydomonas reinhardtii SAS-6 (CrSAS-6) can alter the fold symmetry of structures self-assembled in vitro , including towards 8-fold [ 33 ]. Another possibility is based on the finding that although wild-type CrSAS-6 favors self-assembly of 9-fold symmetrical structures, in vitro , 8-fold and 10-fold symmetrical ring-structures can be observed in addition to 9-fold symmetrical ones [ 33,34 ]. Such observations have led to the suggestion that peripheral elements must function together with SAS-6 ring-containing structures to select strictly 9-fold radially symmetrical entities [ 33,35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Compatible with this notion, rational mutagenesis of Chlamydomonas reinhardtii SAS-6 (CrSAS-6) can alter the fold symmetry of structures self-assembled in vitro , including towards 8-fold [ 33 ]. Another possibility is based on the finding that although wild-type CrSAS-6 favors self-assembly of 9-fold symmetrical structures, in vitro , 8-fold and 10-fold symmetrical ring-structures can be observed in addition to 9-fold symmetrical ones [ 33,34 ]. Such observations have led to the suggestion that peripheral elements must function together with SAS-6 ring-containing structures to select strictly 9-fold radially symmetrical entities [ 33,35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Why are these key centriole assembly proteins present at such low concentrations? Several of these proteins have a tendency to self-assemble into larger macromolecular structures (Stevens et al, 2010b; Montenegro Gouveia et al, 2018; Kim et al, 2019; Gartenmann et al, 2020), so it seems likely that their low cytoplasmic concentration helps to ensure that they normally only start to form a cartwheel at the single kinetically favourable site on the side of the mother centriole (Lopes et al, 2015; Banterle et al, 2021). Indeed, our FCS data suggests that the concentration of Sas-6 in the embryo is low enough that it is largely monomeric in the cytoplasm, even though it is almost certainly incorporated into the centriole cartwheel as a dimer (Kitagawa et al, 2011; van Breugel et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…These concentrations are similar to the MS estimates in human cell lines (Bauer et al, 2016), suggesting that the early embryo does not store a large surplus of any of these proteins. As many of these building blocks have a tendency to selfassemble into larger structures (Stevens et al, 2010b;Montenegro Gouveia et al, 2018;Kim et al, 2019;Gartenmann et al, 2020) this low cytoplasmic concentration presumably helps to ensure that these proteins only assemble into macromolecular structures at the kinetically favourable site defined by Plk4 on the side of the mother centriole (Lopes et al, 2015;Banterle et al, 2021).…”
Section: Core Centriole Duplication Proteins Are Present At Low Conce...mentioning
confidence: 99%
“…This might be aided by interacting proteins such as SAS-5 (44, 48, 50), or by a connection of SAS-6[C] to microtubules. Alternatively, properties of the centriole surface from which the procentriole assembles might impose a different conformation, since the presence of a surface can help constrain the inherent helical properties of Chlamydomonas reinhardtii SAS-6 polymers into a ring (51).…”
Section: Discussionmentioning
confidence: 99%
“…However, the potential evolutionary pressure leading to conservation of such chirality is not clear, although an appealing possibility is that this could be optimal for ciliary and flagellar motility. Regardless, it has been suggested that centriolar chirality may be imparted by inherent chiral features of SAS-6 proteins, with chirality in the inner part of the organelle dictating that of more peripheral elements, including microtubules (51). Alternatively, chirality could stem from the fact that microtubules of the procentriole grow with a fixed orientation from the surface of the centriole, with the plus end leading.…”
Section: Discussionmentioning
confidence: 99%